Pengaruh Reputasi Perusahaan dan Kualitas Pelayanan terhadap Retensi Pelanggan dengan Kepuasan sebagai Variabel Intervening pada Maskapai Penerbangan Sriwijaya Air Semarang - Panjaitan, Bill Ovid; Farida, Naili; Listyorini, Sari (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
The purpose of this study is to determine the effect of the company's reputation and quality of service to customer retention and satisfaction as an intervening variable in the airline Sriwijaya Air Semarang . This type of research is explanatory , with the technique of collecting data through a questionnaire. The sampling technique used purposive sampling technique , the sample of 100 peoples who are service users airline Sriwijaya Air Semarang . The method of analysis used in this study is Part Analiyst or Path Analysis.Based on the calculations show that there is a variable corporate reputation , quality of service , and satisfaction positive and significant impact on customer retention is equal to 21.0 % . Based on the analysis of pathways directly influences have a greater value than the indirect effect , it shows the customer will be immediately have a sense of retention of the services of the airline Sriwijaya Air flight.